Children of mentally ill parents—a pilot study of a group intervention program - Christiansen, Hanna; Anding, Jana; Schrott, Bastian; Röhrle, Bernd (Frontiers in Psychology, 2015)
The transgenerational transmission of mental disorders is one of the most prominent risk factors for the development of psychological disorders. To date there are only a few evidence based intervention programs for this group overall and hardly any in Germany. We translated the evidence based Family Talk Intervention by Beardslee (2009) and adapted it for groups. In a quasi-experimental design three groups are compared: an intervention group (Family Talk Intervention group: n = 28), a Wait Control group (n = 9), and a control group of healthy children (n = 40). Children of mentally ill parents showed higher rates of internalizing/externalizing disorders before and after the intervention compared to children of parents with no disorders. Post intervention children’s knowledge on mental disorders was significantly enhanced in the Family Talk Intervention group and externalizing symptoms were reduced for this group as well. This pilot study of a group intervention for children of mentally ill parents highlights the importance of psycho-education on parental mental disorders for children. Long-term effects of children’s enhanced knowledge about parental psychopathology need to be explored in future studies.